HER2 Genetic Heterogeneity in Gastric Cancer: Evaluation According to the College of American Pathologists Breast Cancer Criteria. Issue 9 (October 2015) - Treacy, Ann D.; Karamchandani, Jason R.; Streutker, Catherine J.; Grin, Andrea
Abstract : Gastric and gastroesophageal junction (GEJ) adenocarcinomas have been shown to display significant HER2 genetic heterogeneity (GH). This is typically seen as a cluster of HER2-positive cells but can also take the form of intermingled cells, referred to a "mosaic" pattern. GH is not well defined in gastric/GEJ tumors and the "mosaic" pattern has never been studied. We sought to evaluate the frequency and distribution of the "mosaic" pattern of GH in gastric/GEJ tumors using the College of American Pathologists-endorsed breast criteria of 5% to <50% amplified nuclei. We also postulated that the lower limit of this GH definition might be seen by chance in normal gastric epithelium. A total of 360 consecutive gastric/GEJ tumors were tested for HER2 by immunohistochemistry and in situ hybridization. Individual tumor cell HER2:CEP17 ratios were calculated for each case and the percentage of tumor cells with a ratio ≥2.0 determined. In addition, 300 normal gastric epithelial cells were scored for HER2 and CEP17 signals. Overall, 265 cases (73.4%) showed GH. The percentage of amplified cells in GH cases linearly correlated with the overall HER2:CEP17 ratio. In normal gastric epithelium, a cell with an "amplified" 2:1 ratio was seen in 9.7% (29/300) of cells, thus reaching GH. The chance of "GH" in scoring 20 normal epithelial cells was 87%. We conclude that GH is very common in gastric/GEJ tumors when College of American Pathologists breast criteria are applied and the lower threshold is likely of little clinical significance due to the finding "amplified" 2:1 nuclei in normal cells.